1976
DOI: 10.1007/bf03186796
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion in the Ni−Cr−Al and Co−Cr−Al systems to 1200°C determined by high-temperature X-ray diffraction

Abstract: The effect of temperature on the lattice parameters of phases in twelve nickel-chromiumaluminum (Ni-Cr-Al) alloys and nine cobalt-chromium-aluminum (Cc-Or-Al) alloys was determined using high temperature diffraction (HTXRD). The temperature range was from 25 to 1200°C. The data for each phase of each alloy were computer fit to an empirical thermal expansion equation developed in this study: 25°C and a value for R was derived for each. Excellent fits were obtained for nearly all cases.A comparison of R value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Analogously, the increase in the Al content of the g phase is associated with an increase in the lattice parameter of the g phase (Table IV), and a decrease in the volume fraction of the g phase (the volume fraction of NiY-rich phases is smaller than 1 pct and is virtually unaffected by LSM). The lattice parameter changes are in agreement with literature data for ternary NiCrAl alloys, [27,28] which show an increase in the lattice parameters of the g and b phases if Cr is replaced by Al (Al has a larger atomic radius than Cr and Ni [29] ). The increase in the volume fraction of b phase within the LSM zone corresponds well with the reduced partitioning of Al, Cr, and Co between the g and b phases (i.e., the image *Taking into account the coarse b, and ignoring the needlelike g precipitates ( Figure 3).…”
Section: Table IV Lattice Parameter a (In Pm) Of The ␥ And ␤ Phases supporting
confidence: 90%
“…Analogously, the increase in the Al content of the g phase is associated with an increase in the lattice parameter of the g phase (Table IV), and a decrease in the volume fraction of the g phase (the volume fraction of NiY-rich phases is smaller than 1 pct and is virtually unaffected by LSM). The lattice parameter changes are in agreement with literature data for ternary NiCrAl alloys, [27,28] which show an increase in the lattice parameters of the g and b phases if Cr is replaced by Al (Al has a larger atomic radius than Cr and Ni [29] ). The increase in the volume fraction of b phase within the LSM zone corresponds well with the reduced partitioning of Al, Cr, and Co between the g and b phases (i.e., the image *Taking into account the coarse b, and ignoring the needlelike g precipitates ( Figure 3).…”
Section: Table IV Lattice Parameter a (In Pm) Of The ␥ And ␤ Phases supporting
confidence: 90%
“…It is known that the presence of a separate alloy α-chromium phase with its very different coeffi- cient of thermal expansion 15 can promote spallation during temperature cycling.…”
Section: Cyclic Oxidationmentioning
confidence: 99%
“…Lowell et al 51 reported the coefficients of thermal-expansion (CTE) for the different phases in the Ni-Cr-Al system using high-temperature X-ray diffraction during the course of a single run. The mean CTEs reported for a,c/c¢, and b phases in a similar alloy were 13 Â 10 )6 , 17 Â 10 )6 , and 19 Â 10 )6 /°C, respectively.…”
Section: Resultsmentioning
confidence: 99%